CLIMATE CHANGE AND ENVIRONMENTAL PROTECTION (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article provides a comprehensive analysis of the water resource challenges facing Uzbekistan, emphasizing the impacts of climate change, inefficient irrigation practices, and increasing water demand. The study highlights the inefficiencies in agricultural water use, which accounts for over 80% of consumption, and identifies potential solutions such as drip and sprinkler irrigation, modernization of infrastructure, and improved water monitoring systems.